Case Report: Prenatal Whole-Exome Sequencing Identified a Novel Nonsense Mutation of the KCNH2 Gene in a Fetus With Familial 2q14.2 Duplication - Zhuang, Jianlong; Chen, Chunnuan; Wang, Yuanbai; Zeng, Shuhong; Chen, Yu’e; Jiang, Yuying; Xie, Yingjun; Wang, Gaoxiong (Frontiers in Genetics, 2022)
Background: Mutations in KCNH2 gene was associated with long QT syndrome 2 (LQT2), which typically manifest a prolonged QT interval and may lead to recurrent syncopes, seizure or sudden death. Limited reports with the mutations in KCNH2 manifest LQT2 combined with tetralogy of fallot. Here, we present an additional case of LQT2 in a fetus with a novel mutation in KCNH2 gene who also coexisting of tetralogy of fallot. Case presentation: Enrolled in this study was a 23-year-old pregnant woman from Quanzhou Fujian province China, with fetal congenital heart defects including tetralogy of fallot, coronary sinus enlargement, and persistent left superior vena cava. No chromosome abnormality was detected by fetal karyotype analysis. An uncertain variant of 238.1-kb duplication in 2q14.2 region contains GLI2 gene was observed in the fetus using chromosomal array analysis, which was inherited from the mother with normal clinical feature. Further whole exome sequencing (WES) elicited a novel nonsense mutation of c.1907C>G (p.S636*) in KCNH2 gene in the fetus, and classified as likely pathogenic variant according to the ACMG guidelines. Conclusion: In this study, we believe that the duplication of 2q14.2 may be a polymorphism variant, and the nonsense mutation in KCNH2 gene may explain the congenital heart defects in the fetus. In addition, we further confirms the application value of WES technology in prenatal genetic etiology diagnosis of fetus with structural anomalies and unexplained structural variants.